Factors Affecting Taxpayers’ Satisfaction with E-Filing Tax System of Books and Stationery in Butwal Sub-Metropolitan City - Ghimire, Shahas Sharma (Kalika Journal of Multidisciplinary Research, 2025)
This study aims to identify and analyze the key determinants influencing taxpayer satisfaction with the electronic filing (e-filing) system of Books and Stationery Business in Rupandehi district. It applies the Information System (IS) Success Model to evaluate the impact of prior experiences with the Inland Revenue Department (IRD), confidence in government websites, and trust intechnology on user satisfaction. A quantitative research approach was employed using a structured questionnaire. Total populations are 236 out of them 195 distributed survey questionnaires, 136 valid responses were collected from taxpayers in Rupandehi district. Simple random sampling technique is used. Statistical tools SPSS and PLS SEM were used to assess the relationship between trust in technology, website quality, service quality, information quality and users’ levels of satisfaction. The analysis revealed that all four factors service quality, information quality, and trust in technology, positively affect taxpayer satisfaction however, IRD website quality is not significant. Among these, information quality has the most consistent and significant influence on both trust and satisfaction, highlighting the importance of clear and accurate content. The study recommends that the IRD enhances the quality of information on its platforms and build stronger relationships with taxpayers to improve overall satisfaction and trust. This research provides original insights by applying the IS Success Model in Nepal’s e-governance context, offering empirical evidence on user perceptions of digital tax services in a developing region.